Corticostriatal signatures of schadenfreude: evidence from Huntington's disease. Issue 1 (1st August 2017) - Baez, Sandra; Pino, Mariana; Berrío, Mildred; Santamaría-García, Hernando; Sedeño, Lucas; García, Adolfo M; Fittipaldi, Sol; Ibáñez, Agustín
Abstract : Schadenfreude — pleasure at others' misfortunes—is a multidetermined social emotion which involves reward processing, mentalising and perspective-taking abilities. Patients with Huntington's disease (HD) exhibit reductions of this experience, suggesting a role of striatal degeneration in such impairment. However, no study has directly assessed the relationship between regional brain atrophy in HD and reduced schadenfreude. Here, we assessed whether grey matter (GM) atrophy in patients with HD correlates with ratings of schadenfreude. First, we compared the performance of 20 patients with HD and 23 controls on an experimental task designed to trigger schadenfreude and envy (another social emotion acting as a control condition). Second, we compared GM volume between groups. Third, we examined brain regions where atrophy might be associated with specific impairments in the patients. While both groups showed similar ratings of envy, patients with HD reported lower schadenfreude. The latter pattern was related to atrophy in regions of the reward system (ventral striatum) and the mentalising network (precuneus and superior parietal lobule). Our results shed light on the intertwining of reward and socioemotional processes in schadenfreude, while offering novel evidence about their neural correlates.